2021
DOI: 10.3892/etm.2021.10858
|View full text |Cite
|
Sign up to set email alerts
|

Pueratin improves diminished ovarian reserve by inhibiting apoptosis

Abstract: Pueratin (Pue) is an extract from Pueraria lobata, and exhibits therapeutic effects for the treatment of inflammation. However, the beneficial effects and mechanisms underlying Pue in the treatment of diminished ovarian reserve (DOR) remains to be fully elucidated. The aim of the present study was to investigate the effect of Pue on Bcl-2 and Bax protein expression in rats with DOR, associated with infertility within clinical practice, induced by 4-vinylcyclohexene diepoxide (VCD). A model of DOR was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The assessment of ovarian reserve plays a crucial role in predicting female fertility. In In addition to granulosa cell apoptosis, abnormal proliferation and differentiation of these cells contribute to the sensitization of follicles to atresia, which is considered an accepted mechanism in the pathogenesis of DOR (35). The histopathological findings from our study revealed a significant increase in the number of primary, primordial, and atretic follicles.…”
Section: Discussionmentioning
confidence: 50%
“…The assessment of ovarian reserve plays a crucial role in predicting female fertility. In In addition to granulosa cell apoptosis, abnormal proliferation and differentiation of these cells contribute to the sensitization of follicles to atresia, which is considered an accepted mechanism in the pathogenesis of DOR (35). The histopathological findings from our study revealed a significant increase in the number of primary, primordial, and atretic follicles.…”
Section: Discussionmentioning
confidence: 50%
“…The inclusion of puerarin in the diet of aged laying hens has been shown to enhance egg production and improve laying performance [ 21 ]. Furthermore, a study conducted on rats found that oral administration of puerarin significantly reduced apoptosis, thereby ameliorating the decline in ovarian reserve function [ 20 ]. However, no effect of puerarin on sow reproductive performance was found.…”
Section: Discussionmentioning
confidence: 99%
“…Puerarin (99%) was purchased from Yunnan BioBioPha Co., Ltd. (Kunming, Yunnan Province, China). The daily intake amount of puerarin was based on the relevant literature on mice [ 20 ] and laying hens [ 21 ]. Dietary composition ( Table 1 ) during gestation and lactation was in accordance with National Research Council (2012) recommendations [ 22 ] From gestation until 1 week prior to parturition, 2.4 kg of ration was provided per day (08:00 and 16:00).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies show that age >35 years and shortened menstrual cycle are indicative of DOR. Currently, no specific clinical drugs are available for DOR, and DOR management mostly relies on hormone therapy in Western countries, which results in increased risks of endometrial cancer and cardiac diseases in the long run [5]. Coenzyme Q10, also known as ubiquinone, is a fat-soluble, natural vitamin-like substance found in many organisms.…”
Section: Introductionmentioning
confidence: 99%